2019
DOI: 10.1016/j.psyneuen.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal psychopathology and stress and offspring HPA axis function at 6 years

Abstract: Our results suggest that maternal psychopathology and stress during pregnancy are associated with long-term HPA axis activity of the offspring. The association of maternal psychopathology and stress during pregnancy with offspring hair cortisone levels is a novel finding. Future studies should examine whether these psychophysiological differences between exposed and non-exposed children underlie offspring morbidity associated with maternal psychopathology and stress during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 63 publications
1
30
1
Order By: Relevance
“…25,26 Maternal HPA axis functioning and its influence on the foetus Altered HPA axis activity in mothers who suffer from severe psychiatric disorders can influence the foetus through intrauterine programming of the HPA axis. 19,27 There is some evidence that these early alterations in HPA axis functioning contribute to vulnerability to psychiatric disease in offspring later in life, 28 by early fine-tuning of the HPA axis set point.…”
Section: Hpa Axis and Psychiatric Disordersmentioning
confidence: 99%
“…25,26 Maternal HPA axis functioning and its influence on the foetus Altered HPA axis activity in mothers who suffer from severe psychiatric disorders can influence the foetus through intrauterine programming of the HPA axis. 19,27 There is some evidence that these early alterations in HPA axis functioning contribute to vulnerability to psychiatric disease in offspring later in life, 28 by early fine-tuning of the HPA axis set point.…”
Section: Hpa Axis and Psychiatric Disordersmentioning
confidence: 99%
“…A similar sex-dependent association between prenatal maternal cortisol and newborn telomere length has also been reported recently (Enlow et al, 2019). Studies of self-reported maternal prenatal stress have also shown sex-specific associations, for example, in a publication from the Generation R cohort (n = 2546) mothers’ prenatal stress assessed as life events and long-standing difficulties predicted increased hair cortisol levels at age 5 years in girls but not boys (Molenaar et al, 2019). In a study with both self-reported and objective stress measurement, following mothers pregnant during the Iowa floods (n = 94), maternal prenatal stress was associated with increased cortisol reactivity in girls but not boys at age 2.5 years (Ping et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The detailed processes are as follows (see, e.g., Molenaar et al, 2019;Bock et al, 2015). When pregnant mothers experience unexpected adverse events or a stressful environment, the hypothalamus (the H of HPA) in the brain area release excessively a type of hormone called corticotropin-releasing hormone (CRH).…”
Section: Stress and Cognitive Deficiencymentioning
confidence: 99%
“…There are also other mediation pathways to explain the association, but the one with HPA axis is commonly accepted.2 Various biological literature tries to find biomarkers to quantify the activity of the HPA axis and the prenatal stress, such as hair cortisone levels (see, e.g.,Molenaar et al, 2019) and dehydroepiandrosterone (DHEA) and dehydroepiandrosteronesulfate (DHEAS) (see, e.g.,Schmelter et al, 2019).…”
mentioning
confidence: 99%